Groundwater in Arid and Semi-Arid Areas - Lhoussaine Bouchaou; Mohamed El Alfy; Margaret Shanafield; Abdelfettah Siffeddine; John Sharp (Geosciences)
MDPI has published two issues on groundwater in arid and semi-arid areas in Geosciences [...]